Incomplete recovery of ecosystem processes after two decades of riparian forest restoration. Issue 5 (21st April 2016) - Matzek, Virginia; Warren, Shawn; Fisher, Colleen
Abstract : Restoration of ecosystem processes such as carbon storage and nutrient cycling may lag behind the restoration of structural attributes of ecosystems, such as species richness and biomass. We used a replicated chronosequence of reforested sites on the Sacramento River floodplain to ask if ecosystem processes had reached functional equivalence with nearby remnant forest patches. We found that live and dead biomass pools had mostly recovered to remnant forest levels within two decades of replanting, but soil carbon and nitrogen stocks, rates of CO2 efflux, N availability, and nutrient‐use efficiency still differed significantly between restored and remnant forests. Reforested sites are thus still functionally distinct from remnants despite similarities of vegetation structure.